When to consider takotsubo cardiomyopathy in menopausal elderly woman presenting chest pain - Aziz, Indra Jabbar; Rohman, Mohammad Saifur (Heart Science Journal, 2025)
Background:  An elderly menopausal woman presenting with chest pain in the emergency department may have coronary artery disease (CAD), Takotsubo cardiomyopathy, or other conditions. It is crucial to conduct a thorough diagnostic evaluation in menopausal elderly woman. Case illustration: A 77-year-old postmenopausal woman presenting with first-onset chest pain after having familial issues and severe psychological stress was admitted to the emergency department. She had no identifiable risk factors for CAD, and her physical examination revealed no significant abnormalities. The electrocardiogram (ECG) indicated non-specific ST-segment elevation in leads V3-V6. Serial ECGs showed an evolution of ST-segment elevation that did not align with the typical pattern observed in STEMI. Despite the elevation in cardiac enzymes in the previous hospital, unfortunately, serial cardiac enzymes were inconsistently normal in our hospital. Therefore, these findings implied that the patient's condition might not be ACS, and we cannot rule out the possibility of Takotsubo syndrome. The patient underwent coronary angiography (DCA) and The DCA results revealed normal coronary with suspicion of apical ballooning of the left ventricle as observed from cine angiography. Subsequent echocardiography demonstrated apical akinesis with basal hyperkinesis, the large area of dysfunctional myocardium extending beyond the territory of a single coronary artery and characteristic apical ballooning resembling an octopus trap, consistent with the diagnosis of Takotsubo syndrome. The patient was managed conservatively with supportive care. Her symptoms improved, and she was discharged after five days. Conclusion: This case highlights the importance of considering takotsubo cardiomyopathy in menopausal elderly woman with no risk factor of CAD presenting with chest pain after having psychological stress.